STRATEGI BERTAHAN HIDUP WANITA PEMULUNG DI TEMPAT PENAMPUNGAN SEMENTARA (TPS) KEC.SENAPELAN, KOTA PEKANBARU - Sipahutar, Desti Angelina; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The job of collecting used goods and food scraps from garbage piles is often referred to as scavengers. In research at Senapelan TPS, Pekanbaru, almost all who work as scavengers are women. Working as scavengers is done by them because their family's economic conditions are not fulfilled, so they as wives must also help their husbands to find additional income. Subjects in this study were 5 people, for the determination of informants using purposive sampling technique, where the sample was taken deliberately and in accordance with the criteria set by the author. The research method used is descriptive qualitative research methods. The theory used is the theory of survival strategies, which aims to determine the socioeconomic conditions of women scavengers, and what survival strategies they are doing. From the results of research in the field, women scavengers apply three survival strategies, namely an active strategy by increasing working hours, a passive strategy by applying a frugal lifestyle in the family, and a network strategy by establishing good relationships with relatives, neighbors, and formal relationships. other. Keywords: Scavengers, Survival Strategy